Manufacturability of a Tetraethyl Orthosilicate-Based Hydrogel for Use as a Single Application Otitis Externa Therapeutic - Emma Barrett-Catton; Elizabeth M. Arrigali; Bogdan A. Serban; Kolton C. Sandau; Monica A. Serban (MDPI AG, 2022)
Otitis externa, also known as outer ear infection, is a frequent affliction in both humans and animals. The most prevalent treatment for otitis externa is ear drops, but it is difficult to adhere properly to this treatment, causing poor patient compliance and the potential for complications. As a result, we have developed a tetraethyl orthosilicate-based hydrogel for use as single application treatment for otitis externa to increase ease of use and improve patient outcomes. Herein, we investigated the manufacturability of the hydrogel, focusing on several key aspects: formulation repeatability and reproducibility, material source and tolerances, release of a variety of model drugs, and impact of application-specific physiological factors, specifically local pH and enzymatic activity on drug release. Overall, our results indicate that these hydrogels are well suited for production and scalability, as they have a robust manufacturing process, have a wide tolerance for pH level, release a variety of model drugs, and are not impacted by outer ear canal-specific physiological factors.